An Efficient RFID Tag Estimation Method Using Biased Chebyshev Inequality for Dynamic Frame Slotted ALOHA - Elsaid Ibrahim, Hazem Abdelaal Ahmed; Kenawy, Hamed; Robert, Jörg; Heuberger, Albert (2014 European Conference on Smart Objects, Systems and Technologies, Smart SysTech 2014, 2014)
Radio Frequency Identification (RFID) is a wireless technology allowing for the automatic identification of tags (transponders). For the efficient identification in case of large tag populations, the RFID reader has to precisely estimate the number of tags in the reading area. Inaccuracies in this estimation lead to significantly increased reading times. Therefore, this paper proposes a novel tag estimation technique called biased Chebyshev inequality tag estimation method. This new method improves the existing Chebyshev inequality method by using a collision coefficient. This collision coefficient is calculated numerically using a two dimensional curve fitting approach. The proposed estimation method is compared to two common tag estimation methods in RFID systems. Simulation results of the proposed algorithm show a reading time reduction for large populations of approx. 25%.